A comprehensive kinetic model for phenol oxidation in seven advanced oxidation processes and considering the effects of halides and carbonate. (1st January 2022) - Huang, Kuan; Zhang, Huichun
Highlights: A comprehensive kinetic model was developed for 7+ AOPs with 540+ reactions. Intermediates were considered for the tuning and validation of the model. The effect of anions on the reactivity followed PDS/CuO > H2 O2 /UV > other PDS/PMS. Anions affected the importance of different reactions based on sensitivity analysis. This model can be easily applied to many complex AOPs and different contaminants. Abstract: As one of the most powerful approaches to mechanistically understanding complex chemical reactions and performing simulations or predictions, kinetic modeling has been widely used to investigate advanced oxidation processes (AOPs). However, most of the available models are built based on limited systems or reaction mechanisms so they cannot be readily extended to other systems or reaction conditions. To overcome such limitations, this study developed a comprehensive model on phenol oxidation using over 540 reactions, covering the most common reaction mechanisms in nine AOPs—four peroxymonosulfate (PMS), four peroxydisulfate (PDS), and one H2 O2 systems—and considering product formation and the effects of co-existing anions (chloride, bromide, and carbonate). Existing models in the literature were first gathered and then revised by correcting inaccurately used reactions and adding other necessary reactions. Extensive model tuning and validation were next conducted by fitting the model against experimental data from both this study and the literature. The effects of anions were found to follow PDS/CuO > H2 O2 /UV > other PDS or PMS systems. Halogenated organic byproducts were mainly observed in the PMS systems in the presence of halides. Most of the 543 reactions were found to be important based on the sensitivity analysis, with some anions-involved reactions being among the most important, which explained why these anions substantially altered some of the reaction systems. With this comprehensive model, a deep understanding and reliable prediction can be made for the oxidation of phenol (and likely other phenolic compounds) in systems containing one or more of the above AOPs. Graphical abstract: Image, graphical abstract